Pengaruh E-WOM, Information Quality, dan Brand Trust Terhadap Purchase Intention (Studi pada Calon Konsumen Mixue) - Elsya Dwi Rahmawati; Nindria Untarini (Jurnal Ilmu Manajemen, 2023)
This study analyses the effect of e-wom and information quality on purchase intention with brand trust as the mediating variable of research on Mixue. This research is quantitative research. The sampling technique was used judgmental sampling technique with total 220 respondents. The questionnaire distribution was excecuted online using a Likert scale as an answer measurement tool. The statistical analysis used in this research is Path Analysis with AMOS software version 24. The results showed that the e-wom and information quality variables had a positive and significant effect on purchase intention. The results of this study also showed that the e-wom and information quality variables have a positive and significant effect on purchase intention through brand trust as a mediating variable. This was confirmed in the mediation test which states that the brand trust variable strengthens the influence of the e-wom variable and information quality on purchase intention with the results of the mediating role partially proven (partial mediating). Mixue is expected to continue to build and create good and positive e-wom, provide quality information to potential customers in order to increase purchase intention..